The Importance of Quality Antenatal Care in Improving Maternal and Infant Health - Maria Doresia Sidabungke; Lita Anggraini; Hasta Sulistyaningrum; Viedya Wildan; Wili Sulfiah (Greenation Publisher & Yayasan Global Research National, 2025)
Antenatal care (ANC) is a key intervention to improve the health of pregnant women and their infants. The quality of ANC not only involves the early detection of pregnancy complications but also includes preventive measures, nutritional counseling, maternal mental health support, and the promotion of safe delivery. Evidence shows that high-quality ANC reduces maternal mortality (MMR) and infant mortality (IMR), as well as prevents preterm birth, low birth weight (LBW), and stunting. This narrative review highlights that adherence to the World Health Organization (WHO) standard of a minimum of eight ANC visits during pregnancy significantly contributes to better maternal and infant outcomes. Moreover, the quality of interactions between health providers and mothers, including comprehensive information sharing, is a critical determinant of ANC effectiveness. Therefore, improving the quality of antenatal care should be a priority in health policies, supported by competent health professionals, equitable access to services, and stronger community awareness of the importance of regular pregnancy check-ups.